P04.87 Delineating the invasive component of human brain tumors using brain organoids. (19th September 2018) - Zhou, W; Klink, B; Lunavat, T R; Miletic, H; Joesph, J V; Han, M; Bahador, M; Wang, J; Bjerkvig, R
Abstract: Background: We have previously developed a brain organoid system based on the development of fetal rat brain cells taken from fetuses at the 18th day of gestation. The purpose of the present work was to use the latest technologies to assess in detail the differentiation of various neural cell lineages into mature brain organoids and also to assess their cellular organization into mature brain structures. We also explored in detail glioma cell invasion parameters such as speed of invasion, the clonal composition of invasive cells as their transcriptional profiles. Material and Methods: Western blot, immunohistochemistry, and immunofluorescence were used to detect the expression and distribution of mature neurons, astrocytes, oligodendrocytes, and microglia in the brain organoids at different stages of development. Transcriptomic analysis was also assessed by RNA-seq. To determine the invasive potential of the tumor cells into the organoids, we barcoded various tumor cell clones in order to establish a "rainbow" tumors where different clones were given a different color. By advanced imaging we tracked in real time the invasion of the barcoded cells. Moreover, tumor cells from the invasive areas as well as from the tumor core were analyzed by RNA-seq. Results: Western blots showed that markers of mature neurons, astrocytes, oligodendrocytes and microglia were highly expressed at 14-21th day of brain organoid development, which was also reflected by RNA-seq. Having described in detail the mature organoid structure, we explored the invasive capacity and speed of invasion of the barcoded cells. Our results show that the average speed of glioma cell invasion is in the range of 20 μm/h. We also show that that different glioma stem cell lines show different invasive capacities based on the tumor of origin. Genomic analysis of invasive cells revealed clear invasive signatures. Conclusion: We found that brain organoids display a highly cellular and structural organization. For the first time the speed of invasion was determined as well as their clonal composition. By a molecular identification of invasive and non-invasive cells new therapeutic strategies can be designed targeting the invasive compartment in GBMs.